The Effect of Taxpayer Knowledge, Tax Socialization and Tax Sanctions on the Voluntary Disclosure Program - Tutty Nuryati (Sekolah Tinggi Manajemen IPMI, 2022)
This study aims to examine the effect of taxpayer knowledge, tax socialization and tax sanction on the Voluntary Disclosure Program (VDP). This purpose used a sample of 97 respondents. The data analysis method used is Partial Least Square (PLS) with SmartPLS ver.3.3.9 data analysis tool. This research is a type of research that uses a quantitative approach, because the data used is in the form of numbers and is calculated by statistical methods. The data used is primary data. Primary data was obtained by a list of questions in the form of a structured questionnaire with the aim of collecting data or information from respondents in the Bekasi City and Regency area. The results of this study also explain that (1) taxpayer knowledge has a positive and significant effect on VDP, (2) tax socialization has a positive and significant effect on VDP, (3) tax sanction has a positive and significant effect on VDP. The results of this study also show that the variables of taxpayer knowledge, tax socialization and tax sanctions affect the Voluntary Disclosure Program (PPS) by 45.6%, the remaining 54.4% is influenced by other variables outside of this study.